Both partial inactivation as well as activation of NF-κB signaling lead to hypertension and chronic kidney disease - Zhang, Xiaotan; Wang, Guang; Li, Ming; Li, Yunjin; Luo, Xin; Liu, Yvonne; Zhang, Xiaoli; Hocher, Johann-Georg; Krämer, Bernhard; Hocher, Berthold; Yang, Xuesong (Nephrology, dialysis, transplantation, 2024)
Activation of nuclear factor-kappa B (NF-κB) signalling is key in the pathogenesis of chronic kidney disease (CKD). However, a certain level of NF-κB activity is necessary to enable tissue repair.The relationship between activated and inactivated NF-κB signaling and the pathogenesis of CKD was investigated using mouse models of NF-κB partial inactivation (mutating cysteine at position 59 of the sixth exon on the NF-κB gene into alanine) and activation (mutating cysteine at position 59 of the sixth exon on the NF-κB gene into serine).The density of CD3, CD8, CD68 positive cells, as well as the expression of interleukin 6, Tumor necrosis factor receptor associated factor 1 and Nef-associated factor 1 in the kidney tissues of NF-κBC59A mice were reduced, whereas an opposing pattern was observed in the NF-κBC59S mice. Blood pressure, kidney fibrosis (analyzed by periodic acid-Schiff, Masson trichrome and Sirius Red staining, as well as α-SMA immunofluorescence), serum creatinine and urinary albumin-to-creatinine ratio are markedly increased in NF-κB-activated and -inactivated mice compared with controls. Transmission electron microscopy indicated that the glomerular basement membrane was thicker in both NF-κBC59A and NF-κBC59S mice compared with wild-type mice.Using mice models with partially activated and inactivated NF-κB pathways suggests that there is an apparently U-shaped relationship between blood pressure, kidney function as well as morphology and the activation of the NF-κB pathway. A certain optimal activity of the NF-κB pathway seems to be important to maintain optimal kidney function and morphology.